2016
DOI: 10.3389/fpls.2016.01555
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Expression and IAA-Amide Synthetase Activity Analysis of Gretchen Hagen 3 in Papaya Fruit (Carica papaya L.) during Postharvest Process

Abstract: Auxin plays essential roles in plant development. Gretchen Hagen 3 (GH3) genes belong to a major auxin response gene family and GH3 proteins conjugate a range of acylsubstrates to alter the levels of hormones. Currently, the role of GH3 genes in postharvest physiological regulation of ripening and softening processes in papaya fruit is unclear. In this study, we identified seven CpGH3 genes in a papaya genome database. The CpGH3.1a, CpGH3.1b, CpGH3.5, CpGH3.6, and CpGH3.9 proteins were identified as indole-3-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…To explore the evolutionary relationships of the GH3 genes from the three species of Brassica and A. thaliana , a phylogenetic tree was generated with 19 A. thaliana , 38 B. rapa , 25 B. oleracea , and 66 B. napus members, which would contribute to understanding the potential roles of the GH3 genes in Brassica species. The phylogenetic tree was divided into three groups (I, II, and III), and this pattern of three groups for the GH3 genes in the phylogenetic tree was in line with previous reports [23,24,46]. Group III possessed the highest number of the GH3 members (Figure 3).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To explore the evolutionary relationships of the GH3 genes from the three species of Brassica and A. thaliana , a phylogenetic tree was generated with 19 A. thaliana , 38 B. rapa , 25 B. oleracea , and 66 B. napus members, which would contribute to understanding the potential roles of the GH3 genes in Brassica species. The phylogenetic tree was divided into three groups (I, II, and III), and this pattern of three groups for the GH3 genes in the phylogenetic tree was in line with previous reports [23,24,46]. Group III possessed the highest number of the GH3 members (Figure 3).…”
Section: Resultssupporting
confidence: 88%
“…The GH3 proteins play important roles in plant development and light signal pathways [18,19,20,21]. So far, the identification and analysis of the GH3 gene family have been performed in different plant species, such as Arabidopsis thaliana , rice, maize, Medicago truncatula , Carica papaya , and so on [12,17,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…These ethylene-related genes may play important roles in the abnormal softening and coloration that occur in papaya fruit upon chilling 31 . Many works have demonstrated that GH3, ARF, and Aux/IAA protein families are also involved in papaya fruit postharvest processes 20 , 23 , 32 . In our study, at least one crotonylation site in each ethylene- (ACO1/2/3 and ACS) and auxin (ARF, AUX1, TIR and GH3)-related enzyme has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the physiological parameters of papaya fruit were performed according to the previous study [15]. Three biological replicate were used.…”
Section: Methodsmentioning
confidence: 99%
“…Papaya ( Carica papaya L.), a climacteric fruit widely planted and consumed, displays quick softening and a short shelf-life [15, 16]. Once the climacteric fruit is mature, its soft texture and susceptibility to pathogenic fungi make the storage life short [17].…”
Section: Introductionmentioning
confidence: 99%